Building Ethiopia’s food security resilience to climate and hydrological change - Murgatroyd, Anna; Thomas, Timothy S.; Koo, Jawoo; Strzepek, Kenneth M.; Hall, Jim (IOP Publishing, 2025)
Historically Ethiopia's food security has been sensitive to climatic variability, but changes in future weather and climate could lead to overall reductions and increased variability in agricultural production, without further adaptation. We present an integrated modelling assessment framework which combines climate, crop, and hydrological modelling to quantify future risks to Ethiopia's food security. We explore the impacts of 2°C and higher climate change scenarios on water availability and crop yields and simulate how future climate shocks may impact Ethiopia's food. We consider three adaptations to agricultural management practices (improved seed varieties, increased use of nitrogen fertilizer and supplementary irrigation) and quantify their effectiveness in enhancing the resilience of Ethiopia's food system to climate and hydrological change by 2050. Results show that, without policy intervention, climate change creates a risk of declining Meher season crop yields across Ethiopia. Under the worst climate change scenario, teff (−12.0%), barley (−6.7%), and wheat (−4.4%) are projected to have the largest decline in average yields, whilst maize (−0.1%) and sorghum (+0.9%) yields are less impacted thanks to more favourable growing conditions. However, the results also indicate that the adaptation options have a bigger beneficial effect than the climate impact. Of the policies evaluated, improved seeds have a relatively greater effect than increased fertilizer use. Supplementary irrigation could help to mitigate increases in crop water requirements under warmer climate conditions and is most effective in drought prone basins and for drought-vulnerable crops. Overall, the results show that locally relevant agricultural policies are necessary to build Ethiopia's food system resilience to climate and hydrological change by the mid-century.